2013
DOI: 10.1080/13803395.2013.776010
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in HIV-associated neurocognitive disorders (HAND): The neuropsychological dynamics of time monitoring

Abstract: Strategic monitoring during a delay interval is theorized to be an essential feature of time-based prospective memory (TB PM), the cognitive architecture of which is thought to rely heavily on frontostriatal systems and executive functions. This hypothesis was examined in 55 individuals with HIV-associated neurocognitive disorders (HAND) and 108 seronegative comparison participants who were administered the Memory for Intentions Screening Test (MIST), during which time monitoring (clock checking) behavior was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…At the same time, the very fact that costs were observed under PM conditions indicates that younger HIV+ adults have the capacity to allocate preparatory attentional processes (Smith, 2003) or other types of strategic monitoring (Einstein & McDaniel, 2005) to PM task requirements, as seen in healthy participants (Loft & Remington, 2013). Thus, this pattern of PM performance coalesces with prior clinical studies showing that HIV-associated deficits in event-based PM are driven by strategic rather than automatic processes, including executively-demanding aspects of encoding the cue-intention pairing (Woods et al, 2010) and cue monitoring (Doyle et al, 2013); given that these executive functions are at risk for impairment following HIV infection, degradation of such strategic processes may be the mechanism by which PM impacts real-world outcomes like antiretroviral adherence (e.g., Contardo et al, 2009). …”
Section: Discussionsupporting
confidence: 66%
“…At the same time, the very fact that costs were observed under PM conditions indicates that younger HIV+ adults have the capacity to allocate preparatory attentional processes (Smith, 2003) or other types of strategic monitoring (Einstein & McDaniel, 2005) to PM task requirements, as seen in healthy participants (Loft & Remington, 2013). Thus, this pattern of PM performance coalesces with prior clinical studies showing that HIV-associated deficits in event-based PM are driven by strategic rather than automatic processes, including executively-demanding aspects of encoding the cue-intention pairing (Woods et al, 2010) and cue monitoring (Doyle et al, 2013); given that these executive functions are at risk for impairment following HIV infection, degradation of such strategic processes may be the mechanism by which PM impacts real-world outcomes like antiretroviral adherence (e.g., Contardo et al, 2009). …”
Section: Discussionsupporting
confidence: 66%
“…We considered that an episodic memory component may have contributed to the pattern of deficits observed on the longer PM tasks, however, results of our secondary analyses of RBANS subscales and MIST error types data support our interpretation that the observed PM findings are not an artifact of retrospective memory. Further, previous studies (Doyle et al, 2013; Morgan, Weber, Rooney, Grant, & Woods, 2012; Raskin et al, 2011; Weinborn, Woods, Nulsen, & Park, 2011) using these same PM tasks have demonstrated that long-delay time-based PM is more strongly related to executive dysfunction than retrospective memory in clinical samples. Taken together, we are confident that the interpretation of our primary findings regarding PM cue and delay are not better explained by simple failures in retrospective memory.…”
Section: Discussionmentioning
confidence: 81%
“…The profile of HIV-associated PM impairment is often characterized by decrements in strategic processes (e.g., Doyle et al, 2013), which are associated with greater risk of worse real-world problems, including non-adherence to cART regimens (Woods et al, 2009). The present study examined the potential benefits of a brief future visualization exercise during the encoding stage of a semi-naturalistic event-based PM task for young adults with HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the profile of HIV-associated PM deficits tends to reflect dysregulation of strategic processes. For example, individuals with HIV show decrements in strategic time monitoring (i.e., clock checks) during time-based PM tasks (Doyle et al 2013) and tend to demonstrate large effect sizes for time- versus event-based PM deficits (Martin et al 2007; Zogg et al 2011). Thus it may be that individuals with deficits in the strategic aspects of PM would benefit most from interventions for enhancing PM functioning.…”
Section: Introductionmentioning
confidence: 99%